2020
DOI: 10.25046/aj050684
|View full text |Cite
|
Sign up to set email alerts
|

Automatic License Plate Detection and Recognition for Jordanian Vehicles

Abstract: Jordanian license plates OCR (optical character recognition) rectangularity make of the vehicle Nowadays, automatic number plate recognition (ANPR) is very important especially in the era of smart cities and intelligent transport systems. Fully automated number plate detection and recognition system helps in reducing time, error, and cost for tracking of vehicles and for recording traffic violations. The main goal of this paper is to design a low cost fully automated number plate detection and recognition syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Similarly, the recognition accuracy of American-and European-standard plates are respectively found to be 74.8% and 84% compared to 36.9% and 43.6% for the old ALPR system. The obtained results are also compared to other Jordanian plate-recognition systems reported in [5,6,20]. In [5] the authors used a dataset consisting of only 46 images and reported an overall system accuracy of 70%.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Similarly, the recognition accuracy of American-and European-standard plates are respectively found to be 74.8% and 84% compared to 36.9% and 43.6% for the old ALPR system. The obtained results are also compared to other Jordanian plate-recognition systems reported in [5,6,20]. In [5] the authors used a dataset consisting of only 46 images and reported an overall system accuracy of 70%.…”
Section: Resultsmentioning
confidence: 97%
“…In [5] the authors used a dataset consisting of only 46 images and reported an overall system accuracy of 70%. In [6], the accuracy was 89% for a dataset of 100 images. In [20], an improved accuracy of 87% was reported for a dataset of 187,200 images that was used to train a deep neural network.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations